CARDIOVASCULAR RISK RECLASSIFICATION BY PULSE WAVE VELOCITY IN BRAZILIAN HYPERTENSIVE PATIENTS. (June 2022) - Inuzuka, Sayuri; Filho, Gilberto Guimaraes; Vitorino, Priscila; Barroso, Adriana; Filho, Robson Alves; Melo, Victoria; Urzeda, Luiz; Valle, Deborah; Silva, Eduarda; Mesquita, Gustavo; Sousa, Ana; Coca, Antonio; et al.
Abstract : Objective: Objetive: The number of asymptomatic hypertensive patients who already have subclinical injuries in the early stages of hypertensive disease is high and, generally, they are not identified by the traditional evaluation model. The use of Pulse Wave Velocity (PWV) in addition to traditional cardiovascular risk factors can improve risk stratification. The present study intends to perform the reclassification of cardiovascular risk according to the median Pulse Wave Velocity (PWV) and correlate PWV with the intima-media thickness, with the left ventricular (LV) mass indexed and with microalbuminuria. Design and method: Design and method: Multicenter analytical cross-sectional study of patients undergoing measurement of central and peripheral blood pressure parameters between October/2018 and March/2019. Intima-media thickness (IMT) and presence of carotid plaque, left ventricular mass indexed and microalbuminuria were also evaluated. Fisher's test was applied to verify the association of cardiovascular risk reclassification by median PWV. Spearman's correlation was used to correlate PWV with intima-media thickness, presence or absence of carotid plaque, microalbuminuria and indexed left ventricular mass. A significance level of 5% was adopted. Results: Results: 126 patients were evaluated, with a mean age of 60.58 ± 10.51 years and 87 (69.95%) are women. When reclassified, there was an increase in the frequency of patients who moved from medium to high risk (p<0.001). A weak and positive correlation was identified between PWV and LV mass indexed (r = 0.304, p < 0.001) and with IMT (r = 0.30, p < 0.001). Conclusions: Conclusions: The application of median PWV values is a simple and effective tool to reclassify intermediate-risk individuals to high-risk.